2021
DOI: 10.21203/rs.3.rs-362250/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association Between Carotid Plaque Vulnerability and High Mobility Group Box-1 Serum Levels in a Diabetic Population

Abstract: Background: Carotid atherosclerosis represents one of the complications of diabetes mellitus. In particular, plaque instability contributes to disease progression and stroke incidence. High mobility group box-1 (HMGB1) is a nuclear protein involved in promotion and progression of atherosclerosis and cardiovascular diseases. The aim of this study was to analyze the relationship between HMGB1 serum levels, main inflammatory cytokines, the presence of internal carotid stenosis and unstable plaque in a diabetic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Furthermore, Wang and colleagues demonstrated that LPS/ATP activation of NLRP3 in ammasome stimulates HMGB-1 release leading to cholesterol accumulation in VSMCs and foam cells formation during atherosclerosis, through the downregulation of LXRa and ABCA1 expression (58). HMGB-1 is even responsible of atherosclerotic plaque vulnerability, possibly through VSMCs secretion of matrix metalloproteinase (MMP), enzymes responsible for matrix degradation (32,59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Wang and colleagues demonstrated that LPS/ATP activation of NLRP3 in ammasome stimulates HMGB-1 release leading to cholesterol accumulation in VSMCs and foam cells formation during atherosclerosis, through the downregulation of LXRa and ABCA1 expression (58). HMGB-1 is even responsible of atherosclerotic plaque vulnerability, possibly through VSMCs secretion of matrix metalloproteinase (MMP), enzymes responsible for matrix degradation (32,59).…”
Section: Discussionmentioning
confidence: 99%
“…Different evidences show a role of HMGB-1 in cardiovascular diseases development. It has been associated to coronary artery disease (28-31) and it represents an independent risk factor for carotid plaque vulnerability (32). In addition, we previous observed that levels of HMGB-1 were higher in patients with PAD and diabetes mellitus compared to those without diabetes mellitus (33).…”
Section: Introductionmentioning
confidence: 91%
“…It has been postulated a compensatory, yet often failed, self-defence response of OPG to atherogenesis. On the other hand, OPG can exert pro-inflammatory effects; by increasing macrophage infiltration and leukocyte adhesion to endothelial cells, and sensitizing them to the effects of TNF-alpha via upregulation of angiopoietin-2 [33,34]. RANKL promotes osteogenic differentiation of vascular smooth muscle cell and stimulates the release of various pro-inflammatory cytokines, such as matrix metalloproteinase (MMP)-9, while TRAIL is a potent activator of apoptosis.…”
Section: Osteoprotegerin and Atherosclerotic Pathophysiological Mecha...mentioning
confidence: 99%
“…On the other hand, miR-21 can inhibit VSMC apoptosis by increasing the rate of proliferation of VSMCs in mouse carotid arteries and jointly protecting fibrous cap stability in atherosclerotic plaques [123]. It has been shown that hyperglycemia and streptozotocin-induced type 1 diabetes can reduce the synthesis of collagen and lead to the formation of unstable atherosclerotic plaques in ApoE -/mice [124]. Metformin can increase the level of activator protein 2 alpha (AP-2α) in carotid atherosclerotic plaques in diabetic ApoE -/mice, decrease the expression levels of miR-124, and increase the levels of prolyl-4-hydroxylase alpha 1 (P4Hα1) and collagen in VSMCs.…”
Section: Ncrnas In Vsmcsmentioning
confidence: 99%